Consanguineous‐derived homozygous WNT1 mutation results in osteogenesis imperfect with congenital ptosis and exotropia. Issue 8 (11th June 2020) - Chen, Peng; Chen, Jiaxi; Yang, Zhantao; Lu, Yang; Shen, Liping; Zhou, Kai; Ye, Shenyi; Shen, Bo
Abstract: Background: Wnt signaling pathway plays an important role in promoting ostergenesis. WNT1 mutations have been considered as a major cause of ostergenesis imperfect (OI). We identified an OI patient with pathogenic consanguineous‐derived homozygous WNT1 missense mutation. Methods: We designed and applied a panel of known 261 genes associated with hereditary bone diseases for targeted next‐generation sequencing to examine clinically diagnosed OI patients. Detected mutations were confirmed by Sanger sequencing. Results: The female proband presented with severe OI with low bone density, multiple long bone fractures, short stature, and absence of dentinogenesis imperfect and brain malformation. She had congenital ptosis and exotropia with her left eye, and absence of blue sclera. The proband came from a consanguineous family and had a homozygous WNT1 missense mutation (c.677C>T, (p.S226L)). In addition, three other compound heterozygous mutations (c.1729C>T in FKBP10, c.1958A>C in FGFR3, c.760G>C in TRPV4) were also detected in her family members. Conclusion: We report the first identified case of consanguineous derived homozygous WNT1 mutation leading to severe osteogenesis imperfecta with congenital ptosis and exotropia. Abstract : We report the first case of consanguineous‐derived homozygous mutation in a lady affected with severe osteogenesis imperfecta, congenital ptosis, and exotropia of her left eye. The c.677C>T, (p.S226L) mutation in WNT1 has been confirmed to be a novel mutation.